Procedural Content Generation pada Game Tower Defense menggunakan Perlin Noise dan Algoritma Floyd Warshall - Hans Juwiantho; Liliana Liliana; Michael Budiono (Journal of Animation and Games Studies, 2023)
To distinguish each level, tower defense games require map design, enemy travel routes, and enemy wave designs. Manually designed designs require a lot of effort and time. To overcome this problem, procedural content generation is used to create maps automatically. Not all content can be created automatically, the content designed in this research includes portal design, tower design, enemy design, and tile design. The Map is created automatically using Perlin Noise to determine the type of tiles on the map. To produce a playable map in accordance with the minimum distance requirement of 45 tiles, the position of the player portal and enemy portal need to be checked using the Floyd-Warshall algorithm. The test results show that after 100 attempts, 25 trials need to be repeated because the distance between the portals does not meet the requirements. The average map creation time is 0.99 seconds. The enemy waves on each map also vary from the number of each type and the order in which the enemies come out.